Evidence for enhanced distal tubule sodium reabsorption in chronic salt-depleted dogs. - Chou, S Y (1976)
In order to assess the renal tubular site(s) at which sodium reabsorption is enhanced in chronic sodium-depletion, seven normal dogs, six salt-depleted dogs, and three normal dogs receiving aldosterone were studied during a steady-state water diuresis under Pentothal anesthesia and during progressive hypotonic saline diuresis. For both maintenance of the water diuresis and progressive hypotonic saline diuresis 0.45% NaCl was used. During the steady state water diuresis delivery of sodium to the diluting segment of the nephron as approximated by solute-free water clearance + sodium clearance/glomerular filtration rate (CH2O + CNa/GFR) was significantly lower in salt-depleted dogs compared to normal dogs with or without aldosterone. During progressive hypotonic saline infusion fractional free water excretion (CH2O/GFR) was similar in all three groups as CH2O + CNa/GFR increased up to 12-14 ml/min-100 ml GFR. Thereafter, CH2O/GFR continued to rise in virtually a straight line in salt-depleted dogs but leveled off in normal dogs with or without aldosterone. These data demonstrate that enhanced sodium reabsorption in the diluting segment of the nephron is an important determinant of the renal sodium retention in chronic extracellular volume contraction in dogs in addition to confirming the presence of increased proximal tubule sodium reabsorption in these animals.